2021
DOI: 10.1007/s40121-021-00518-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Corticosteroid Use in Coronavirus Disease 2019 (COVID-19): A Systematic Review and Meta-Analysis

Abstract: Introduction We conducted a comprehensive literature review to synthesize evidence for the relationship between corticosteroid use and mortality in patients with COVID-19. Methods The PUBMED, EMBASE, and Cochrane Library were searched from inception to March 13, 2021. We searched and analyzed randomized controlled trials (RCTs) and observational studies (OSs) that examined corticosteroid use in patients with COVID-19. The primary outcome was in-hospital mortality, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…From our cohort, patients using corticoids at the time of recruitment were twice as likely to experience a severe COVID-19 infection. Although the use of corticosteroids was not helpful against the SARS and MERS-CoV diseases (Varghese et al, 2020 ; Cui et al, 2021 ), corticosteroids still are recommended as a treatment for only moderate, severe, and critical SARS-CoV-2 infection (National Institutes of Health, 2020b ; Cui et al, 2021 ; Patel et al, 2021 ; Ro et al, 2021 ). The dose used and duration of treatment with corticosteroids remains contentious.…”
Section: Discussionmentioning
confidence: 99%
“…From our cohort, patients using corticoids at the time of recruitment were twice as likely to experience a severe COVID-19 infection. Although the use of corticosteroids was not helpful against the SARS and MERS-CoV diseases (Varghese et al, 2020 ; Cui et al, 2021 ), corticosteroids still are recommended as a treatment for only moderate, severe, and critical SARS-CoV-2 infection (National Institutes of Health, 2020b ; Cui et al, 2021 ; Patel et al, 2021 ; Ro et al, 2021 ). The dose used and duration of treatment with corticosteroids remains contentious.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was hypothesized that steroids may be an effective treatment for COVID-19 patients given their well-known anti-inflammatory and immunosuppressor effects. Several trials have been conducted to confirm this hypothesis [17,18,20,22]. The RECOVERY study is an openlabel trial that includes a high number of patients treated with dexamethasone 6 mg once daily (n = 2104) or with standard care (n = 4321), showing that the steroid administration may reduce the 28-day mortality, especially in patients receiving oxygen support (with both non-invasive and invasive ventilation) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone is preferred over other corticosteroids for its shown efficacy in HLH but there are several other trials reporting positive results with the use of other agents like methylprednisolone in equivalent total daily doses of dexamethasone 6 mg/day (methylprednisolone 32 mg daily or prednisone 40 mg 1 https://www.idsociety.org/covid-19-real-time-learning-network/therapeutics-and-interventions/corticosteroids/ daily) [42][43][44]. Methylprednisolone 250 to 500 mg daily pulses for 3-6 consecutive days has also been shown to improve survival in severe COVID-19 patients [45,46]. Hydrocortisone would be one of the options although its efficacy seemed to be lower than dexamethasone [46].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Methylprednisolone 250 to 500 mg daily pulses for 3-6 consecutive days has also been shown to improve survival in severe COVID-19 patients [45,46]. Hydrocortisone would be one of the options although its efficacy seemed to be lower than dexamethasone [46]. The open-label STOIC trial showed that, an inhaled steroid, budesonide 400 μg twice a day until symptom resolution, decreased the need for urgent medical care in mild patients with early COVID-19 [47].…”
Section: Corticosteroidsmentioning
confidence: 99%